Possible Uses of counterfactual thought experiments in History - Alexander Maar (Principia: An International Journal of Epistemology)
Counterfactual thought experiments in history have become increasingly popular in the last two decades, and a new and controversial branch of history has originated from their use: counterfactual history, also known as virtual history. Despite its popularity amongst the general public, most academic historians consider historical counterfactuals as having little epistemic value. This paper investigates three alleged uses of counterfactual thinking in historical explanations: (1) the claim that counterfactual thinking gives historians useful insights; (2) that it is a useful tool to evaluate an event’s causal significance; (3) that it shows much of history to be essentially ‘chaotic’. I argue that only (2) convincingly justifies the use of counterfactual thought experiments in history, as it allows historians to illustrate how they perceive events’ degrees of sensitivity to changes to their causal history, being an important part of providing a causal explanation.